Experimental investigation of phase equilibria in the Tb-Si-Cr system. (June 2019) - Huang, X.M.; Hu, T.; Liu, S.H.; Cai, G.M.; He, Y.H.; Jin, Z.P.
Abstract: Tb-Si intermetallics have been recognized as interesting magnetic and electrical materials. The addition of Cr can modify the property and broaden the application of Tb-Si intermetallic compounds. Understanding phase relations, phase stability and microstructural changes of relative systems are essential for tuning and improving performance of this type of materials. In this work, phase relationships in the Tb-Si-Cr ternary system have been studied based on phase and microstructure identification of key equilibrated alloys. Isothermal sections of this system at 1273 K and 1073 K were experimentally constructed by means of electron probe microanalysis, X-ray diffraction, and differential thermal analysis. As one of results, the ternary compound TbSi2 Cr2 was confirmed to exist at both 1273 K and 1073 K. In addition, remarkable solubilities of the third element were detected in some binary compounds. The solubility of Cr in Tb2 Si3-δ and TbSi at 1273 K are about 4.0 and 9.1 at%, respectively. The solubility of Cr in Tb5 Si3 increases from 3.0 at% at 1273 K to 6.2 at% at 1073 K. Besides, the compound Tb2 Si3-δ were determined to be stable ranging from 1098 ± 25 K to 1513 ± 10 K, based on the analysis of microstructure. Moreover, the annealing temperature dependence of micro-hardness for Tb2 Si3-δ intermetallic phase was investigated by nano-indentation. Highlights: Isothermal sections at 1073 and 1273 K of Tb-Si-Cr ternary system were determined. Differing from other R-Si intermetallics, a certain amount of Cr was confirmed to be dissolved in Tb-Si compounds. The stable temperature ranges of Tb2 Si3-δ were determined from 1098 ± 25 K to 1513 ± 10 K. The primary crystal region of ternary compound TbSi2 Cr2 exists in liquidus projection. Annealing temperature dependence of micro-hardness for Tb2 Si3-δ intermetallic phase was investigated.